The Duty of Care in Czech Company Law - Kateřina Eichlerová (Acta Universitatis Carolinae. Iuridica, 2022)
The duty of care is a core instrument to incentivise directors to act diligently and in the best interest of the company. The article seeks to answer the following questions concerning the duty of care in company law; 1) who is obliged to exercise it, 2) to whom, 3) what is the content of the duty of care, 4) what place does it occupy among other standards of care, 5) what is its nature, and 6) how does the duty of care differ between a director of a company and director of other legal persons of private law.